PEMANFAATAN LIMBAH KULIT PISANG KEPOK (Musa paradisiaca forma typica) SEBAGAI PUPUK ORGANIK CAIR (POC) SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MATERI BIOTEKNOLOGI KELAS XII SMA - Khoirunnisya Dalimunthe; Imam Mahadi; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Kepok banana skin waste is organic waste that has not been managed properly. Management of kepok banana skin waste can be used as Liquid Organic Fertilizer (POC). To see the macro nutrient content, namely N, P and K on the POC kepok banana skin, an analysis of the content of N, P and K. was applied. The application of POC was applied to lettuce plants (Lactuca sativa). This study aims to determine the optimal concentration of POC kepok banana skin based on the content of N, P and K and to determine the optimal concentration of POC application of kepok banana skin to lettuce plants. This research uses a quantitative approach with two types of research Complete Completely Randomized Design (CRD). The results showed that without the addition of EM4 it had shown the highest mean for testing the content of N, P and K and its application to lettuce plants. It was concluded that the optimal concentration without addition of EM4 from kepok banana skin waste used as POC based on the content of N, P and K was at treatment K1 and there was the addition of EM4 in treatment K5. The optimal concentration of giving POC kepok banana skin without the addition of EM4 to lettuce plants (Lactuca sativa) was in treatment I1 and without the addition of EM4 was at treatment I5.Key words : Kepok Banana Skin Waste, Effective Microorganism 4, Molasses and Lettuce Plants